К вопросу о соответствии видов русских приставочных глаголов туркменским эквивалентам - Іванова, Т.А.; Винниченко, С.Д.; Мурадова, М.; Иванова, Т.А.; Винниченко, С.Д.; Мурадова, М.; Ivanova, T.A.; Vinnichenko, S.D.; Muradova, M. (Харківський національний університет імені В.Н. Каразіна, Центр міжнародної освіти, 2010)
В статье дается сопоставительный анализ глаголов совершенного и несовершенного видов русского и туркменского языков.
ДО ПИТАННЯ ПРО ВІДПОВІДНІСТЬ ВИДІВ РОСІЙСЬКИХ ПРЕФІКСАЛЬНИХ ДІЄСЛІВ ТУРКМЕНСЬКИМ ЕКВІВАЛЕНТАМ
Russian Prefix Verbs and their Equivalents in the Turkmen Language
Russian prefix verbs and their equivalents in the Turkmen language are examined in the article. The analysis of some aspects of the subject matter understudy is given
Keywords: verb; aspect; prefix; глагол; вид; приставка; дієслово; вид